R&D and non-linear productivity growth of heterogeneous firms - D'Artis Kancs; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2012)
The present paper studies the relationship between R&D investment and firm productivity growth by explicitly accounting for non-linearities in the R&D-productivity relationship and inter-sectoral firm heterogeneity. In order to address these issues, we employ a two step estimation approach, and match two firm-level panel data sets for the OECD countries, which allows us to relax both the linearity and homogeneity assumptions of the canonical Griliches (1979) knowledge capital model. Our results suggest that: (i) R&D investment increases firm productivity with an average elasticity of 0.15; (ii) the impact of R&D investment on firm productivity is differential at different levels of R&D intensity - the productivity elasticity ranges from -0.02 for low levels of R&D intensity to 0.33 for high levels of R&D intensity; (iii) the relationship between R&D expenditures and productivity growth is non-linear, and only after a certain critical mass of R&D is reached, the productivity growth is significantly positive; (iv) there are important inter-sectoral differences with respect to R&D investment and firm productivity - high-tech sectors' firms not only invest more in R&D, but also achieve more in terms of productivity gains connected with research activities.
Keywords: C14; C21; D24; F23; O32; 330; R&D investment; firm productivity; generalised propensity score; Industrielle Forschung; Produktivität; Branche; Vergleich; OECD-Staaten